Brief reflections on the lack of impact of female or mixed Freemasonry in Italian society - Locci, Emanuela (2020)
This paper analyses the impact that female or co-masonry has had on Italian society today. We shall research the ability of obediences to communicate with secular society. As there are no specific studies on the subject, we have used an empirical survey with questionnaires to certify the average Italian’s knowledge of female Freemasonry. Then, through a series of interviews with members of the institution, we explain the results, and present the characteristics of female or co-masonry. Furthermore, we have included a chart of the different Obediences that included women or were mixed lodges in Italy.